The Use of Educational Comics to Increase Reading Interest of Grade V Students at SDN 1 Bayan in the 2024/2025 Academic Year - Aryantika, Denda Sapti; Fitriana, Maulida Arum; Eliyana, Eliyana (International Journal of Education, Information Technology, and Others, 2025)
This study aims to increase the reading interest of grade V students at SDN 1 Bayan in the 2024/2025 academic year. The subjects of this study were fifth grade students at SDN 1 Bayan with a total of 35 students, namely 14 male students and 21 female students. The research method used is the Classroom Action Research Method (PTK), which is a study conducted systematically on various actions taken by teachers to improve learning conditions. The data in this study were collected using the observation method as the main method, interviews and documentation methods as complementary methods. The results of this study indicate that there is an increase in students' interest in reading using educational comic media in class V. It is marked by an increase in the percentage of students' interest in reading. Marked by an increase in the percentage of students' interest in reading activities in classical completeness of 42% (pre-cycle) increased to 57% in (cycle 1) and increased significantly to 85% in (cycle II). This shows an increase in students' interest in reading with a percentage of 85%, which has been achieved in this study. Which means that most students experience an increase in reading interest using educational comics at SDN 1 Bayan, West Bayan Hamlet, Bayan Village, Bayan District, North Lombok Regency, 2024/2025 School Year.